When Work Follows You Home: How Relationship Satisfaction Moderates the Link between After-Hours Smartphone Use and Work-Life Conflict - Liew, Hui Chang; Sheilla Lim, Omar Lim (HRMARS, 2026)
This empirical investigation analyzes the extent to which personal relationship satisfaction serves as a moderating variable in the connection between work-related smartphone utilization during non-working hours and the resultant work-life conflict. The data were obtained via an online survey targeting 109 Malaysian administrative and diplomatic officials situated in Sarawak. The findings indicate a statistically significant positive correlation between work-related smartphone usage after hours and work-life conflict, with excessive professional smartphone engagement outside of standard working periods being associated with an increase in work-life conflict. Furthermore, moderation analysis elucidates that personal relationship satisfaction plays a crucial role in diminishing the detrimental effects of after-hours work-related smartphone use on work-life conflict. These results imply that organizations ought to foster supportive environments that facilitate employees in delineating clear boundaries between their occupational and personal spheres. The study concludes by offering suggestions for prospective research trajectories within this domain.